Ear Infection and Its Associated Risk Factors in First Nations and Rural School-Aged Canadian Children. (10th February 2016) - Karunanayake, Chandima P.; Albritton, William; Rennie, Donna C.; Lawson, Joshua A.; McCallum, Laura; Gardipy, P. Jenny; Seeseequasis, Jeremy; Naytowhow, Arnold; Hagel, Louise; McMullin, Kathleen; Ramsden, Vivian; Abonyi, Sylvia; et al.
Abstract : Background. Ear infections in children are a major health problem and may be associated with hearing impairment and delayed language development. Objective. To determine the prevalence and the associated risk factors of ear infections in children 6–17 years old residing on two reserves and rural areas in the province of Saskatchewan. Methodology. Data were provided from two rural cross-sectional children studies. Outcome variable of interest was presence/absence of an ear infection. Logistic regression analysis was conducted to examine the relationship between ear infection and the other covariates. Results. The prevalence of ear infection was 57.8% for rural Caucasian children and 43.6% for First Nations children living on-reserve. First Nations children had a lower risk of ear infection. Ear infection prevalence was positively associated with younger age; first born in the family; self-reported physician-diagnosed tonsillitis; self-reported physician-diagnosed asthma; and any respiratory related allergy. Protective effect of breastfeeding longer than three months was observed on the prevalence of ear infection. Conclusions. While ear infection is a prevalent condition of childhood, First Nations children were less likely to have a history of ear infections when compared to their rural Caucasian counterparts.